First record of Vanellus vanellus (Linnaeus, 1758) (Aves, Charadriidae), Northern Lapwing, in Malaysia at the southernmost occurrence of the species’ range - Mohd Ros Effendi; Mohammad Saiful Mansor (Check List)
Vanellus vanellus (Linnaeus, 1758) (Aves, Charadriidae), Northern Lapwing, is listed as Near Threatened by the IUCN due to declines in the availability of its habitat since 1980. The species is a widespread Palearctic breeder and an uncommon migrant to Southeast Asia, where it winters in Thailand and Vietnam. We document the first recorded sighting of V. vanellus in Malaysia, marking the southernmost occurrence of the species to date.